Durability Studies on Fly Ash Based Geopolymer Concrete Incorporated with Slag and Alkali Solutions - S. Nagajothi; S. Elavenil; S. Angalaeswari; L. Natrayan; Wubishet Degife Mammo (Advances in Civil Engineering)
This study explores the durability of green cementitious material of geopolymer concrete. Geopolymer concrete is produced from the polycondensation reaction of aluminosilicate materials (fly ash, Ground Granulated Blast furnace Slag (GGBS)) with alkaline activator solutions. Geopolymer concrete has excellent mechanical properties and its production requires low energy and results in low levels of CO2 emission. Due to the high demand for river sand, manufactured sand is used as a replacement material in geopolymer concrete under ambient curing conditions. In this study, the durability of G30 grade geopolymer concrete has been investigated using tests acid resistance, water absorption, sulphate resistance, Rapid Chloride Penetration Test (RCPT), and rate of absorption (Sorptivity) test. The sulphuric acid, sodium sulphate, and water absorption tests were carried out at 28 days, 56 days, and 90 days for both the geopolymer and the conventional concrete. The reduction percentage in water absorption and compressive strength loss was found to be better in geopolymer concrete than in conventional concrete. Geopolymer concrete’s chloride penetrability and rate of absorption were analogous to conventional concrete. Regression analysis for geopolymer and conventional concretes in the rate of absorption test showed a good relationship between absorption and the square root of time.